Effectiveness of Government Policies in the Development of Sustainable Tourism Destinations (A Case Study of Danau Biru, Karang Sidemen Village, Batukliang Utara Subdistrict, Central Lombok Regency) - Andika, Esa Dwi; Mintasrihardi; Sulhan Hadi (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
The development of sustainable tourism requires effective government policies, especially for village-based tourist destinations. This study aims to analyze the effectiveness of government policies in the development of the Danau Biru (Blue Lake) tourism destination in Karang Sidemen Village, Central Lombok Regency, as well as to identify the factors that influence the effectiveness of these policies. This research uses a qualitative descriptive approach with data collection techniques including observation, in-depth interviews, and documentation. The research informants include village government officials, managers of the Village-Owned Enterprises (BUMDes), representatives from the Tourism Office, and local community members around the tourism destination. Data analysis is conducted using the Miles and Huberman interactive analysis model, while data validity is ensured through source and technique triangulation. The research findings indicate that the policy for developing Danau Biru tourism has not been fully effective. This is marked by a gap between planning and policy implementation, limited infrastructure and supporting facilities, weak coordination among stakeholders, and suboptimal promotion and community participation within the framework of sustainable tourism. This study highlights the importance of strengthening institutional capacity, improving human resource capacity, and fostering multi-party collaboration in improving the effectiveness of village-based tourism destination development policies.